The The Effect of the Talking Stick Cooperative Learning Model on Biology Learning Outcomes at SMA Negeri 1 Waingapu - Maria Wanda; Vidriana Oktoviana Bano; Anita Tamu Ina (Universitas PGRI Adi Buana Surabaya, 2023)
This study aims to determine the effect of the Talking Stick Cooperative Learning Model on Biology Learning Outcomes at SMA Negeri 1 Waingapu. This type of research is a quasi-experimental design using a nonequivalent control group design with a quantitative approach. Sampling using purposive sampling. The population in this study were students of class XI MIPA in the odd semester of the 2022/2023 academic year. The sample of this study was 37 students of class XI MIPA 1 as the control class and 37 students of XI MIPA 5 as the experimental class. The results of the descriptive analysis obtained showed that the average pre-test and post-test scores for the experimental class were 61.76 <76.89. Meanwhile, the average value - average pre-test and post-test control class 58.81 <69.81. Testing the hypothesis using a paired sample t-test produces an Asymp value. Sig (2-tailed) 0.000 means the value is less than 0.05 (<0.05). It can be concluded that the talking stick cooperative learning model affects learning outcomes